Characterizing myths of sexual aggression in the young population in Spain - Belén Sanz Barbero; Carmen Vives-Cases; Laura Vall-llosera Casanovas; Laura Serra Saurina; María Carme Saurina Canals; Gemma Renart Vicens (BMC, 2024)
Abstract Background Myths of sexual aggression have a negative influence in aggressive behavior against women, in the institutional approaches to sexual violence and in how women cope with it. The objective of this study is to describe acceptance of myths of sexual aggression in young women and men residing in Spain. Method Cross-sectional study carried out online with 2,515 women (50.2%) and men (49.8%) ages 18-35 in Spain in 2020. Information on myths was collected using the Acceptance of Modern Myths About Sexual Aggression Scale (AMMSA). We described the myths most prevalent among women and men. The variables associated with myths were identified using multiple regression. The regression models were adjusted by sociodemographic and sexual orientation variables. Results The average AMMSA values were higher among men [mean: 3.11; standard deviation (sd):1.23] than among women (mean 2.49 sd:1.11). In both sexes, the myths with greater acceptance showed the presence of patriarchal gender roles in sexual contacts. Men were more likely than women to accept myths that question allegations and severity of violence. Having a higher level of educational studies (β -0.350 sd: 0.046) was associated with lower average AMMSA values. Being born in Latin America (β 0.047 sd: 0.063) was associated with higher average AMMSA values. Among heterosexual men, AMMSA values were greater than among gay and bisexual men. Among women, there was no difference in average AMMSA values based on sexual orientation. Conclusions Myths persist during youth that question and trivialize sexual violence against women. It is necessary to implement strategies that reduce these myths, particularly in heterosexual men, in those of foreign-born origin and among those with low levels of education.